Concept and Factors affecting Well-Being as Perceived by Bangkok Homebuyers - Sumitra Wongpakdee; Piyarat Nanta; Benjamas Kutintara (Environment-Behaviour Proceedings Journal, 2023)
This exploratory study aims to: [1] explore how the Bangkok home buyers define the notion of well-being and [2] identify the built environment and socioeconomic attributes that the home buyers perceived as factors contributing to the state of well-being. Research data is collected from thirteen focus group discussions. Results from this research indicated that the informants perceived well-being as a highly positive feeling derived from having good physical and mental health. Factors contributing to well-being included living in a good environment and friendly community, encompassing a comfortable and convenient lifestyle, safety, and appealing built environment design.
Keywords: Psychological Well-being and Life Satisfaction; Place Attachment and Urban Studies; Urban Transport and Accessibility